A comprehensive review on solar cooker with sun tracking system. (2020) - Devan, P.K.; Bibin, Chidambaranathan; Gowtham, S.; Hariharan, G.; Hariharan, R.
Abstract: Nowadays petroleum-based energy sources rule the largest energy consuming domestic sector across worldwide. The energy used for cooking is the most important in the energy consuming sector, and its demand is continuously increasing day by day. Solar energy used for cooking is one of the prominent solutions for meeting the energy demands. However, its large-scale distribution and propagation still remain limited. Among the various solar cooking technologies are exist globally, limited technologies were used. This paper discusses the recent developments of a solar cooking technologies. The detailed review on solar cooking technologies provides an outline on solar cookers developed. Solar parabolic cooker is working on the principle of solar thermal heating system. Solar thermal systems generate heat energy from sun light. Flat-plate solar thermal collectors are used to heat air or a water for space and water heating or drying agricultural products because of producing low temperature (27 °C to 60 °C). The parabolic solar cooker with sun tracking system helps to reduce the need for frequent manual tracking and standing of sun and it increase the performance of the solar cooker with constant heating process. Sun tracking with the help of sensors and microcontroller. Parabolic reflector helps to concentrate the light into a single point on the cooker and the light energy converted into a heat energy. Due to this heating process, food is cooked in the pot.